ENTREPRENEURSHIP EDUCATION IN RUSSIA: DIAGNOSIS OF THE PROBLEM - Yuriy B. Rubin (Moscow Polytechnic University, 2016)
The article describes the state of Entrepreneurship education in Russian educational system and its elements. The author analyzes the challenges and problems, encountered by Russian universities on the way to implement educational programs in Entrepreneurship. Also the author explains approaches used by European, American universities and educational institutions of developing countries, which are not yet in use by Russian universities.